Fungi in archives, libraries, and museums: a review on paper conservation and human health - Pinheiro, Ana (2020)
The action of fungi on books, documents, maps, and works of art on paper can result in inestimable cultural losses. Plus, some of the fungi present in paper documents, surfaces and air from archives, libraries and museums are also a threat to human health. This work aims to review the literature on the most important and frequent microfungal populations found in paper-based collections all over the world, and correlate these data with human health risks. A total of 71 studies, dating between 1997 and 2018 were reviewed and organized. From 27 different countries, 207 fungal genera and 580 species were reported. Chaetomium sp. and Fusarium sp. were found to be special contaminants in the air of archives and have been associated with paper biodeterioration. The most common fungi reported (e.g. Penicillium, Aspergillus, and Alternaria species) have an impact on paper conservation but can also cause adverse human health effects. The most frequent fungal species retrieved from discoloured paper materials are discussed in greater detail. Considerations on methods of identification and quantification of fungal contamination are also presented. Finally, the authors acknowledge an urgent need for standardizing research in this area and further studies are proposed.